SINTESA PEMIKIRAN PARA FILOSOF MUSLIM ERA KLASIK TENTANG PENDIDIKAN ISLAM - Fauziah, Arinal Haq (Cognitive: Jurnal Pendidikan dan Pembelajaran, 2024)
The classical era Muslim philosophers as the main milestone in the creation of philosophy have some thoughts about Islamic education. The synthesis of these thoughts aims to find common ground in order to improve the effectiveness of providing education for mankind. The research used a normative-descriptive method by collecting data on the thoughts of classical era Muslim philosophers, both from written books and electronic media and related journals (library research) which were then observed and critically analysed to find a synthesis of their thoughts. The selection of classical era Muslim philosophers is because compared to contemporary and modern philosophers, classical era Muslim philosophers' knowledge of philosophy is more in-depth because they are the birth of philosophy in Islam. This research results in the alignment of the views of the classical era Muslim philosophers regarding Islamic education which correlates between reason and revelation, making education the foundation of life in the world and the hereafter and emphasising Islamic education on the aspects of morals and morals. In this study, it is hoped that the meeting point of the views of classical era Muslim philosophers can make the basis, foundation, improve and evaluate and improve the effectiveness of Islamic education comprehensively.